1986
DOI: 10.1111/j.1471-4159.1986.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Proton Magnetic Resonance Analysis of Human Cerebrospinal Fluid

Abstract: High‐resolution proton magnetic resonance spectroscopy was used to analyze human cerebrospinal fluid obtained from patients with several neurological problems. The major metabolites measured included glucose, lactate, glutamine, citrate, inositol, acetate, creatine, creatinine, β‐hydroxybutyrate, alanine, and pyruvate. A drug vehicle, propylene glycol, was also measured. Alterations in the cerebrospinal fluid of these metabolites provided information concerning metabolism of the brain. Magnetic resonance spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…The extracellular concentration of these neurochemicals in actual CSF is of the order of mM, for example, glucose 3-4, lactate 1-2 and glutamine 0.2-0.4 mM (Aasly et al, 1997;Garseth et al, 2000;Petroff et al, 1986). The lower concentration of neurochemicals in the microdialysate samples is expected because of the finite flow rate (l/min), the less than perfect exchange efficiency (<95%), and the different diffusion characteristics of different neurochemicals (Benveniste, 1989).…”
Section: H 1d Experimentsmentioning
confidence: 97%
See 1 more Smart Citation
“…The extracellular concentration of these neurochemicals in actual CSF is of the order of mM, for example, glucose 3-4, lactate 1-2 and glutamine 0.2-0.4 mM (Aasly et al, 1997;Garseth et al, 2000;Petroff et al, 1986). The lower concentration of neurochemicals in the microdialysate samples is expected because of the finite flow rate (l/min), the less than perfect exchange efficiency (<95%), and the different diffusion characteristics of different neurochemicals (Benveniste, 1989).…”
Section: H 1d Experimentsmentioning
confidence: 97%
“…NMR spectroscopy can be both qualitative and quantitative, which means chemical components can be identified on the basis of their unique resonance frequencies and their concentrations measured. The aforementioned advantages have resulted in its application in clinical diagnosis of diseases and for the monitoring of subjects during the course of medical treatment (Koschorek et al, 1993;Petroff et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…28,33,34,61 It has recently been observed that the analysis of CSF based on CSF cytology, sugar and protein content is not the primary information to serve for the purpose of differential diagnosis. 25 As noted during the PROTON MR CSF ANALYSIS 221 course of our present investigation, in certain cases, clinical symptoms (as observed by the clinician) were difficult to interpret and it was found that the children were unable to express themselves.…”
Section: Discussion Nmr Spectroscopic Findings and Clinical Observationsmentioning
confidence: 99%
“…27 Besides all these techniques, the analysis of CSF is often crucial for the diagnosis of neurological disorders, as the chemical components of cerebrospinal fluid (CSF) reflect the state of the central nervous system (CNS) in a healthy and diseased state. 28 In recent times, high-resolution proton MR spectroscopy has beyond doubt become one of the most important analytical tools for obtaining metabolic information on biological fluid or tissue extracts. [28][29][30][31][32][33][34][35][36][37][38][39] It has been well documented that NMR spectroscopy gives non-invasive, qualitative and quantitative information regarding the metabolic profile [40][41][42][43][44][45][46][47][48][49][50][51][52] and usually a metabolite concentration of greater than a few mM is detectable in 1 H NMR spectra 53 in a reasonable amount of time ( 1 H NMR; 128 scans; approximately 15 min), and with the recent technological advances in NMR probe design such as microprobes and cryoprobes, the detection range and time taken have been reduced further using high-field magnets, 600 MHz or higher.…”
Section: Introductionmentioning
confidence: 99%
“…Examples are functional studies of bio-macromolecules that are not available in isotopeenriched form, including interaction studies with small ligands in drug design or folding/unfolding studies of proteins. Another example may be the high-throughput NMR analysis of biofluids such as urine [1], blood plasma [2], bile, cerebrospinal fluids [3] and cervical mucus [4].…”
Section: Introductionmentioning
confidence: 99%